Khía cạnh nhiệt động học của phản ứng khử chọn lọc NOxbằng hiđrocacbon khi có mặt oxi - Nhân, Trần Văn; Tiệp, Lê Văn; Sơn, Lê Thanh (Vietnam Journal of Chemistry, 2014)
The selective catalytic Reduction of NOxby hydrocarbon (HC-SCR) in the presence of oxygen over Cu/ZSM-5 in the range of temperature 200 - 500oC has been studiel. It is shown that the temperature at which conversion of NOx reaches its maximal value corresponds to the temperature at which hydrocarbon oxidation is complete. It should be noted that the active temperature region of HC-SCR is lower than that of NO decompositon. The experimental results are explained from the point of view of thermodynamics